(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The continental deposits of the Punta San Andrés Alloformation (Plio-Pleistocene) crop out in the marine cliffs of south eastern Buenos Aires province (Fig. 1). The deposits of this unit have been assigned to different continental sub-environments such as floodplains, fluvial channels and temporary water bodies (Zárate, 1989). The aim of this work is to perform a high-resolution facies and facies association analysis as well as an architectural characterization of the sedimentary bodies cropping out in Baliza San Andrés and Complejo Turístico Chapadmalal (Fig. 1). This information will be used to elaborate a conceptual and dynamic model of the depositional environments present in the Punta San Andrés Alloformation and to define main controlling factors over its accumulation. The study area is located in a typical passive margin controlled by transversal extensional systems that originated rift basins (aulacogens) with very little basaltic magmatism (Ramos, 1996; Parker et al. 2008). This area experienced block rotation due to isostatic equilibrium and sedimentary overload. Accumulation of post-Miocene deposits was favored by a high sedimentary dynamic associated with the rise of the Andean Cordillera (Turic et al. 1996; Parker et al. 2008). More specifically, the study area is located in the southeastern part of the Tandilia Geological Province (Rolleri, 1975, Fig. 1). The pioneer papers on stratigraphy of the Mar del Plata and Miramar marine cliffs were carried out by Ameghino (1908), Frenguelli (1921) and Kraglievich (1952, 1953, 1959) (Figs. 2, 3). The sedimentological characterization of these deposits was made by Teruggi et al. (1956) and Zárate (1989). This last author also proposed an allostratigraphic framework which intended to unify and simplify the late Cenozoic stratigraphy (Fig. 2). The rich vertebrate fauna present in the Punta San Andrés Alloformation and related units was studied since the first contributions by Ameghino (1908). These studies were the basis for the South American Late Cenozoic biostratigraphic scheme (Fig. 2; Marshall, 1985; Cione and Tonni, 1995, 1999). According to Zárate (1989), the Punta San Andrés Alloformation unconformably overlays the Pliocene continental deposits of the Punta Martínez de Hoz, Playa Los Lobos and Playa San Carlos alloformations. Its lateral extent is about 15 km from the Arroyo Lobería to Punta Vorohué (Fig. 1) and it also crops out between Arroyo Lobería and Playa San Carlos (Fig. 1). The mean thickness of the Punta San Andrés Alloformation is 15 meters. Internally, it is subdivided into three allomembers limited by discontinuity surfaces with a lateral extent that allows mapping them at 1:25.000 scale (Zárate, 1989; Fig. 2). Because of the high mineralogical and textural homogeneity (silty sand and reworked loessoid silt) of the Cenozoic deposits in the study area (Teruggi et al., 1956) the discrimination amongst the different units is based on the abundance of the channelized facies, the carbonatic precipitation and the degree of development and maturity of paleosoils (Zárate, 1989). During field work 10 detailed, 1:50 scaled sedimentological profiles were made at Baliza San Andrés and Complejo Turístico Chapadmalal (Fig. 1) from which the 4 more complete are shown in figure 4. All stratigraphic logs were described in detail and focus was made in grain size, lithology, primary sedimentary structures, bioturbation, fossil content, scale and geometry of the lithosomes; all of these useful features to define sedimentary facies (Reading and Levell, 1996). The abundance of post depositional features (mainly pedogenetic) in the Punta San Andrés Alloformation made necessary the subdivision of sedimentary facies into two groups: depositional and post-depositional. The depositional facies were classified and described according to Miall´s scheme (1978, 2006), which was modified to facilitate their description and interpretation (Table 1). The post-depositional carbonatic facies were described according to Zárate´s scheme (1989) in which the studied features are the geometry of the calcareous accumulation (development in one, two or three dimensions), internal structure, hardness, abundance and lateral extent. The analysis of the seven depositional facies (Table 1) led to interpret a continental environment where unidirectional streams allowed the migration of 3D and 2D dunes as well as the lateral migration of side bars (facies Cig, ACt, ACs, Ah and Ae). It also made clear the presence of paleosoils developed on sheet-flood or splay deposits (facies Alp) and of suspension-related sediments (facies Pm). The analysis of the three post-depositional facies (Table 1) led to the identification of carbonatization processes related to pedogenesis (facies Bc and Tm) and to diagenesis in a vadose environment (facies Tp). The sedimentary facies were grouped into four facies associations (FA; Table 2). Facies associations I and II are related to fluvial channels and FA III and IV are related to floodplains. In the first group, fixed, lowsinuosity channels were differentiated from mobile, high-sinuosity channels based on their symmetric, simple ribbon geometry (Friend et al. 1979; Gibling, 2006) and their constituent facies (Cig, ACt and Ae) as opposed to multiepisodic, complex ribbons (Friend et al., 1979) with participation of Cig, ACt, ACs, Ah and Ae facies. The floodplain associations were divided in crevasse-splay and calcic paleosoils associations. The first one is composed of Alp facies, has a wedge-like geometry, a coarsening-upward arrangement, laterally related to fixed, low-sinuosity channels and a lateral extension over 3 kilometers (Figs. 10a, b). The former is mainly composed of Tp and Tm facies, has a tabular geometry, also laterally related to fixed, low-sinuosity channel and a lateral extension of hundreds of meters. Even though these four facies associations can be found all over the Punta San Andrés Alloformation, it is possible to identify three different sections (A, B and C, Figs. 9 and 11) in which their arrangement and proportions vary. Each of these sections is associated with specific depositional conditions that determined a characteristic fluvial system. Section A involves the lower and middle allomembers (Fig. 2). It is represented by floodplain deposits (both crevasse-splay and calcic paleosoils associations in a rhythmic arrangement) that are considered to represent a terminal fluvial system. The calcic paleosoils are interpreted to represent a dry and arid climate (Marriott and Wright, 1993; Balin, 2000) under a reduced rate of accommodation creation (Marriott and Wright, 1993; Cleveland et al., 2007). Because of the presence of iron nucleids and clay coatings, the crevasse-splay deposits are interpreted to represent wetter climatic conditions (Davies-Vollum and Kraus, 2001) and developed under a greater rate of accommodation creation (Cleveland et al., 2007). Section B (upper allomember) is also made up of floodplain deposits, although coarser and much more dissected by a larger proportion of complex channels. Hence, they are interpreted as a proximal floodplain. Finally, section C is represented by mobile, highsinuosity channel deposits in such a high proportion that in some parts of the outcrops there is no preservation of floodplain deposits. To summarize, for the Punta San Andrés Alloformation deposits cropping out in Baliza San Andrés and Complejo Turístico Chapadmalal, four facies associations can be proposed based on the facies analysis of the sediments and its geometry. The analysis of these associations allowed definingdepositional environments whose interrelation reflected a progressive change in the paleoclimatic and accommodation conditions, probably related to base-level changes. For section A, climate is interpreted to have been dry and arid and related to low accommodation space. During deposition of section B, climate became wetter and accommodation space was increased. Section C is characterized by a lowering in the local base level that led to negative accommodation with fluvial incision. Deposition of channel fills and floodplain deposits indicate the return of positive accommodation space and wet climate.